Exploring The Impact of English Proficiency and Digital Competence on Academic Achievement : How Critical Thinking Skills Make A Difference - Suhartono, Suhartono; Ausat, Abu Muna Almaududi; Azzaakiyyah, Hizbul Khootimah (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to analyze the impact of English proficiency and digital competence on students' academic achievement, with critical thinking skills as a mediating variable. The research employs a quantitative approach using a survey method and SEM-PLS data analysis to examine the relationships between the variables. A purposive sampling technique is applied to select students meeting specific criteria, resulting in a sample of 122 students from Malang, Indonesia. Data were collected through an online questionnaire. This study reveals that English proficiency and digital competence have a significant impact on students' academic achievement, both directly and through critical thinking skills as a factor that strengthens this relationship. Good English proficiency contributes to better academic outcomes, such as higher grades, task quality, class participation, and presentation skills. Similarly, high digital competence helps students utilize technology for learning and effective communication, which also positively impacts their academic achievement. Interestingly, critical thinking skills play a crucial role in connecting these two factors with academic achievement. This means that students who are capable of critical thinking are more likely to maximize their English proficiency and use of technology, which in turn enhances their academic performance.